Revisiting systematic geographical variations in tonsils surgery in children in the Spanish National Health System: spatiotemporal ecological study on hospital administrative data. Issue 12 (1st December 2022) - Castaño-Riera, Eusebio; Ridao, Manuel; Librero, Julian; Martínez-Lizaga, Natalia; Comendeiro-Maaløe, Micaela; Angulo-Pueyo, Ester; Peiro, Salvador; Bernal-Delgado, Enrique
Abstract : Objective: To provide new evidence on how tonsils surgery in children has geographically varied over time in the context of the Spanish National Health System. Design: Observational ecological spatiotemporal study on geographical variations in medical practice, using linked administrative datasets, including virtually all surgeries performed from 2003 to 2015. Setting: The Spanish National Health System, a quasi-federal structure with 17 autonomous communities (ACs), and 203 healthcare areas (HCAs). Participants: Patients aged 19 and younger residing in the HCAs and ACs. Interventions: Tonsillectomy with adenoidectomy (T&A); and tonsillectomies alone (T). Main endpoints: (1) Evolution of T&A and T rates; (2) spatiotemporal variation in the risk of receiving T&A or T surgery at regional level (ACs) and HCAs; and (3) the fraction of the variation (FV) attributed to each of the components of variation—ACs, HCAs, year and interaction ACs year. Results: T&A age-sex standardised rates increased over the period of analysis from 15.2 to 20.9 (5.7 points per 10 000 inhabitants). T alone remained relatively lower than T&A rates, evolving from 3.6 in 2003 to 3.9 in 2015 (0.3 points per 10 000 inhabitants). Most of the risk variation was captured at the HCAs level in both procedures (FV: 55.3% in T&A and 72.5% in T). The ACs level explained 27.6% of the FV in the risk in T&A versus 8% in T. The interaction ACs year was similar in both procedures (FV: 15.5% in T&A and 17.5% in T). The average trend hardly explained 1.46% and 1.83% of the variation, respectively. Conclusion: Our study showed wide persistent variations with a steady increase in rates and risk of T&A and a stagnation of T alone, where most of the variation risk was explained at HCA level.